Chidamide combined with paclitaxel effectively reverses the expression of histone deacetylase in lung cancer. Issue 7 (August 2020) - Zhang, Na; Sun, Pan; Jin, Haizhen; Yang, Yuqin; Zhao, Qingya; Zhou, Lin; Guo, Lili; Yang, Xiaohua; Lu, Liming
Abstract : The role of histone deacetylases (HDACs) in lung cancer has been extensively studied. Inhibition of HDAC activities have been used as a new cancer treatment strategy. To date, many HDAC inhibitors have been shown to induce apoptosis and inhibit tumorigenesis. Chidamide (CS055) is a new member of HDAC inhibitors. In China, Chidamide has been approved for the treatment of relapsed or refractory peripheral T-cell lymphoma. However, the efficacy of Chidamide in non-small cell lung cancer remains unclear. In this study, we used lung cancer primary cells and investigated the effects of Chidamide combined with paclitaxel on lung cancer. We found that Chidamide combined with paclitaxel effectively inhibited the expression and activity of HDAC in primary lung cancer cells, induced their apoptosis and blocked cell cycle. Chidamide combined with paclitaxel may therefore provide a new promising therapeutic treatment for lung cancer.